2013
DOI: 10.1002/biot.201200391
|View full text |Cite
|
Sign up to set email alerts
|

Current developments in high‐throughput analysis for microalgae cellular contents

Abstract: Microalgae have emerged as one of the most promising feedstocks for biofuels and bio-based chemical production. However, due to the lack of effective tools enabling rapid and high-throughput analysis of the content of microalgae biomass, the efficiency of screening and identification of microalgae with desired functional components from the natural environment is usually quite low. Moreover, the real-time monitoring of the production of target components from microalgae is also difficult. Recently, research ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 91 publications
0
22
0
Order By: Relevance
“…In the attempt to identify algal strains and environmental conditions that promote the accumulation of large amounts of intracellular lipids to be harvested as biofuels and nutraceuticals, a growing body of studies involving batch (Breuer et al, 2012;Griffiths et al, 2012) or high-throughput (Lee et al, 2013) lipid screening techniques has appeared. For instance, nitrogen-limited conditions have repeatedly been shown to promote significant accumulation of neutral lipids for a wide collection of algal strains (Breuer et al, 2012;Griffiths et al, 2012;Erickson and Jimenez, 2013), and elevated PUFA levels have been reported at low light exposure (Thompson et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In the attempt to identify algal strains and environmental conditions that promote the accumulation of large amounts of intracellular lipids to be harvested as biofuels and nutraceuticals, a growing body of studies involving batch (Breuer et al, 2012;Griffiths et al, 2012) or high-throughput (Lee et al, 2013) lipid screening techniques has appeared. For instance, nitrogen-limited conditions have repeatedly been shown to promote significant accumulation of neutral lipids for a wide collection of algal strains (Breuer et al, 2012;Griffiths et al, 2012;Erickson and Jimenez, 2013), and elevated PUFA levels have been reported at low light exposure (Thompson et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Other measurement principles include NMR spectroscopy, FC, GC-MS, high-performance liquid chromatography (HPLC), pyrolysis, and dielectric spectroscopy. A survey of currently used standard offline methods can be found in the publication of Technical Standards Committee of the Algal Biomass Organization [9] and a review on high-throughput analysis methods [8]. A short overview of the advantages and disadvantages of current advanced methods for lipid (triacylglyceride) determination in microalgae is given in [166].…”
Section: Novel Measuring Methods With Potential For Online Monitoringmentioning
confidence: 99%
“…Measurement of fluorescence in the form of 2D fluorometry, spectroscopy in the visible and infrared range, and Raman spectroscopy can be used for estimation of pigment, lipid, and biomass concentration [8,24,35,[171][172][173]. FC could also be adapted for online monitoring of cell size and shape distributions, culture composition, and identification of invaders and of biomass composition, and some attempts in this direction have already been made [117].…”
Section: Novel Measuring Methods With Potential For Online Monitoringmentioning
confidence: 99%
See 2 more Smart Citations